The influence of the post-autotomy regeneration of a sexual trait and mating tactics in a fiddler crab - Ribeiro, Pablo Damián (2024)
Male fiddler crabs own an enlarged claw which is a weapon and an ornament. The enlargement of this claw begins from the juvenile stage and continues throughout life. Males may voluntarily lose (i.e. autotomise) this claw. After several moults males may regenerate a new claw, called leptochelous, which acquires a similar length but a lower muscle mass area than the original one, called brachychelous. In some species, regenerated claws develop permanently as leptochelous, the population having two discrete claw morphologies. Other species present morphological variations with leptochelous and brachychelous being two ends of a continuum. In the species Leptuca uruguayensis, we studied the morphological variation of this enlarged claw, whether it may be caused by its regeneration at different male sizes, and its consequences on mating success. We found that claws could not be discriminated as discrete morphs, suggesting a morphological continuum from brachychelous to leptochelous. Regenerated claws in the laboratory were initially small and proportional to body size, while a field experiment confirmed that claw size is recovered after several moults. Morphological variation may be caused by energetic limitations where males of different sizes must differently trade-off between restitution of claw length (ornament function) or claw muscle area (weapon function). Fiddler crabs use two mating tactics with different levels of female choice. However, regardless of the mating tactic, leptochelous males were at a disadvantage at high densities, while not at low densities, suggesting that the consequences of autotomy and regeneration on mating success may depend on the social context.